Fundamentals of world regional geography - Hobbs, Joseph J. (Joseph John), 1956- (Belmont, ca : Brooks/Cole Cengage Learning, 2013)
Fundamentals of World Regional Geography brings course concepts to life with interactive learning, study, and exam preparation tools along with comprehensive text content for one semester/quarter courses.
Keywords: Geography -- Textbooks; Geography -- Outlines, syllabi, etc; Teaching of specific subjects; Geography